Exploring teachers' approaches to science practical work in lower secondary schools in Malaysia (IR) - Siti Shamsiah Sani (2014)
Practical work in science is a teaching approach that aims to enable students to develop procedural and conceptual understanding and an understanding about the nature of science. Practical work is required by the Malaysian Science Curriculum at all school levels. The purpose of this research was to gain an understanding of teachers' views and practices in conducting practical work in lower secondary schools. This research, which adopted a case study approach, was underpinned by constructivist views of learning and investigated the phenomenon of practical work in three co-educational schools in the state of Melaka. The participants were three science teachers and their classes of about 35 students each. Data were collected through teacher interviews, classroom observations, document analysis and focus group interviews with students. Findings suggest that teachers' understanding about practical work were aligned with their purposes for conducting practical work. Practical work that teachers offered promoted low levels of inquiry and at best students were developing a view that in science we follow a set of procedures to arrive at a well-known conclusion. Teachers' practices were constrained by limited resources, prescribed texts, the amount of content to be taught, and their science content knowledge. Student learning was constrained by the limited exposure to authentic science investigation, low teacher expectation, a focus on hands-on rather than minds-on learning, and the language of instruction. The findings have implications for teacher practice and science education policy for lower secondary schools in Malaysia.